A hydrogel electrolyte and its preparation method and application
By utilizing the Hoffmanster effect and temperature-responsive polymer and combining the ion coordination of metal salts, a physically crosslinked polymer hydrogel electrolyte is constructed, which solves the problem of non-degradability and insufficient processability of gel electrolyte materials in the prior art, and achieves a hydrogel electrolyte with high mechanical strength, recyclability and excellent electrochemical properties.
Patent Information
- Application Number
- CN202411391959.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-10-08
AI Technical Summary
The existing gel electrolyte framework materials are mainly composed of non-degradable synthetic polymers, which lead to environmental pollution and waste of resources during battery recycling. Flexible electronic devices have high requirements for processability and lack high mechanical strength, recyclable and processable gel polymer electrolyte technology.
Two polymers with Hoffmanst effect are used as the hydrogel framework, one of which is temperature-responsive and the other contains characteristic functional groups. Through the ion coordination of metal salts and the Hoffmanst effect, a physically cross-linked polymer hydrogel electrolyte is constructed, and the sol-gel phase transition is controlled by temperature, and the polymer mass ratio is regulated to prepare hydrogel electrolytes with different mechanical strengths and conductivity.
It realizes a bio-friendly, recyclable high-mechanical strength hydrogel electrolyte, which is suitable for water-based metal ion batteries and soft-pack batteries, showing excellent electrochemical performance and electrochemical stability, and is also environmentally friendly and low economic cost.
Smart Images

Figure CN118899557B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic gel electrolytes, and in particular relates to a hydrogel electrolyte and a preparation method and application thereof. Background Art
[0002] Gel polymer electrolytes (GPEs) are polymer electrolytes in which solid and liquid phases coexist, combining the advantages of traditional electrolytes and all-solid polymer electrolytes. Gel electrolytes have a three-dimensional network structure, which gives them high mechanical strength and self-supporting properties, thereby preventing electrolyte loss and electrode short circuits, and improving the safety of electrochemical devices to a certain extent; in addition, gel electrolytes have good molding ability and mechanical adaptability, and can be used in various stretchable and foldable flexible electronic devices. Therefore, they have attracted much attention in the research of high specific energy and high safety solid-state metal batteries. However, most of the reported gel electrolyte skeleton materials are composed of non-degradable synthetic polymers, which will cause environmental pollution and resource waste during battery recycling. In addition, due to the rapid development of personalized flexible electronic devices, more requirements are put forward for the processability of flexible batteries. Therefore, it is urgent to develop new technologies for the preparation of high mechanical strength, recyclable and processable gel polymer electrolytes.
[0003] The Hofmeister effect, also known as the ion-specific effect, refers to the phenomenon that proteins precipitate from water in the presence of salt. By adjusting the content of Hofmeister effect macromolecules (kosmotropes) and chaotropes in ionic solutions, the polymerization state of polymer chains can also be adjusted, thereby affecting the water content and pore structure, and ultimately affecting the performance of the material. The Hofmeister effect has a wide range of applications in materials science. For example, in ion-conductive hydrogels, by adjusting the types and concentrations of kosmotropes and chaotropes, the mechanical strength and ionic conductivity of the hydrogel can be simultaneously regulated. By utilizing the temperature response characteristics of natural polymer materials themselves, the gel electrolyte can be induced to undergo a gel-sol phase transition by changing the temperature, thereby achieving processability.
[0004] Therefore, in terms of raw material selection, Hofmeister effect macromolecules with temperature responsiveness (gelatin, agarose, gellan gum, etc.) and polymers containing characteristic functional groups (such as carboxyl-modified natural polymers, acrylic polymers) are used to construct gel polymer networks. The purpose of electrolyte selection is that cations can form ion coordination with carboxyl groups in hydrogels, and anions have a strong Hofmeister effect. Metal salts with Hofmeister effect are selected as electrolytes and chaotropic agents. Based on the characteristics of gelatin and agarose with temperature responsive gel-sol transition, the gel material can be processed and shaped by heating-cooling methods. Polymers containing carboxyl functional groups can coordinate with metal cations; at the same time, due to the Hofmeister effect, the presence of anions can cause the bound water of the polymer chain to dissociate to form a crystalline region. From the two aspects of ion coordination and the formation of crystalline regions, the mechanical strength and ionic conductivity of the gel can be improved simultaneously. The design of this strategy is simple and efficient, utilizing the inherent temperature responsiveness of the polymer itself and the ionic coordination of the functional groups as well as the Hofmeister effect. It is environmentally friendly, low in economic cost, simple in method, and has a certain degree of universality. It has a good promoting effect on the development of new green and sustainable flexible battery materials. There are currently no related reports in this regard. Summary of the invention
[0005] The technical problem solved by the present invention is to provide a hydrogel electrolyte and a preparation method thereof. The preparation method of the hydrogel electrolyte does not use chemical crosslinking agents and initiators, selects two polymers with Hofmeister effect as hydrogel skeletons, one of which is temperature responsive and the other contains characteristic functional groups, selects metal salts as chaotropic agents and electrolytes, and prepares bio-friendly physically crosslinked polymer hydrogel electrolytes. The sol-gel phase transition is controlled by temperature, and the mass ratio of the two polymers is regulated to finally prepare a series of hydrogels with different mechanical strengths. The obtained hydrogel can be shaped using 3D printing, molds, etc. during the preparation process, and then different concentrations of metal salts are introduced by solvent exchange, and finally a series of hydrogel electrolytes with different mechanical strengths and conductivity are prepared. The hydrogel electrolyte can be used to prepare aqueous metal ion batteries, and the prepared aqueous metal ion batteries show excellent electrochemical performance and electrochemical stability; at the same time, the hydrogel electrolyte can be used to prepare soft-pack batteries, and the prepared soft-pack batteries show excellent stability.
[0006] The present invention adopts the following technical solution to solve the above technical problems: a hydrogel electrolyte, which is constructed by a polymer and a metal salt through the Hofmeister effect, ion coordination synergy and hydrogen bonding, and the metal salt is wrapped in a three-dimensional network of the hydrogel, wherein the hydrogel is cross-linked by a polymer 1 with a Hofmeister effect and a polymer 2 containing characteristic functional groups to form a three-dimensional network structure, the cations in the metal salt are coordinated with the characteristic functional groups in the polymer 2, and the anions in the metal salt are used to promote the formation of a crystalline region between the polymer 1 and the polymer 2, and the structure of the hydrogel electrolyte is as follows Figure 1 As shown, the polymer 1 is one or more of agar, gelatin or gellan gum, the polymer 2 is one or more of sodium alginate, polyvinyl alcohol, polyacrylic acid, carbomer or functionalized chitosan, and the cation in the metal salt is Zn 2+ Mg 2+ 、Al 3+ or Ca 2+ One or more of; the anion in the metal salt is SO4 2- 、S2O3 2- , Cl - , ClO 4- or HPO4 2- One or more of .
[0007] The preparation method of the hydrogel electrolyte described in the present invention specifically comprises the following steps: dissolving polymer 2 in deionized water, adding polymer 1, and then heating to form a uniform polymer solution, completing 3D printing and mold shaping of the polymer solution by controlling the temperature before and after gelation to obtain a hydrogel, and then immersing the obtained hydrogel in a metal salt solution to obtain a hydrogel electrolyte.
[0008] It is further defined that the mass ratio of polymer 1 to polymer 2 is 3-5:1, and the concentration of the metal salt solution is 3-5 mol / L.
[0009] The use of the hydrogel electrolyte described in the present invention in the preparation of aqueous metal ion batteries, since polymer 2 contains carboxyl groups, can improve the electrochemical stability of the aqueous metal battery through the interaction between the carboxyl groups and metal ions in the formed hydrogel electrolyte, thereby making the prepared aqueous metal ion battery exhibit excellent electrochemical performance and electrochemical stability.
[0010] Application of the hydrogel electrolyte of the present invention in the preparation of soft-pack batteries.
[0011] The hydrogel electrolyte of the present invention is treated by soaking in an alkaline solution or an acidic solution to remove crosslinking, thereby realizing the recycling and repeated use of the hydrogel.
[0012] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0013] 1. The present invention selects environmentally friendly natural macromolecules as raw materials, does not use chemical cross-linking agents, and prepares physically cross-linked hydrogels, which can be processed and shaped to meet the needs of personalized customization, and its application range is more diversified.
[0014] 2. The present invention utilizes the Hofmeister effect of the raw materials themselves and the coordination effect of metal cations and characteristic functional groups of hydrogels to effectively improve the mechanical strength of the hydrogel three-dimensional network and increase the service life; and the preparation method of the hydrogel electrolyte of the present invention is simple and low in economic cost.
[0015] 3. The preparation method of the hydrogel electrolyte in the present invention is applicable to a wide range of polymers and has a certain universality.
[0016] 4. The hydrogel electrolyte in the present invention is composed of a reversible physical cross-linked network and can be recycled and reused through simple post-treatment, meeting the national requirements for green and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Figure 2 is the structural diagram of the hydrogel electrolyte.
[0018] Figure 2 A roadmap for the preparation of hydrogel electrolytes.
[0019] Figure 3 This is a diagram showing the processability, mechanical properties and internal crystal structure of GCZ hydrogel electrolyte.
[0020] Figure 4 This is a diagram showing the cycling performance of GCZ hydrogel electrolyte and its application as a soft-pack battery.
[0021] Figure 5 The diagram shows the cycling performance of the recycled GCZ-r hydrogel electrolyte and its application as a soft-pack battery. DETAILED DESCRIPTION
[0022] The following is an example of preparing a hydrogel electrolyte GCZ using gelatin and carboxymethyl chitosan (CMCS) as raw materials, zinc sulfate (ZnSO4) as an electrolyte, and assembling a zinc ion battery to further describe the above content of the present invention in detail. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments, and all technologies implemented based on the above content of the present invention belong to the scope of the present invention. Example 1
[0023] Preparation of hydrogel electrolyte GCZ
[0024] Preparation of hydrogel electrolyte GCZ (preparation route see Figure 2 ):
[0025] Weigh a certain mass ratio of Gelatin and CMCS (taking the mass ratio of Gelatin: CMCS = 4:1 and the solid content of 20wt% as an example). Dissolve 0.2g CMCS in 4mL deionized water, add 0.8g Gelatin after it is completely dissolved, and then heat at 75℃ for 4h to form a uniform polymer solution, then pour the polymer solution into a polytetrafluoroethylene mold and cool it to room temperature for demolding. The obtained hydrogel is named GC hydrogel; the obtained GC hydrogel is soaked in a 4M ZnSO4 aqueous solution for 12h to obtain a GCZ hydrogel electrolyte.
[0026] By changing the mass ratio of Gelatin:CMCS, the concentration of ZnSO4 aqueous solution, and the total solid content of the polymer, the mechanical properties and conductivity of the GCZ hydrogel electrolyte can be regulated, and finally a series of hydrogel electrolytes with different mechanical strength and conductivity can be produced.
[0027] Processability test of GCZ hydrogel electrolyte:
[0028] When the concentration of the polymer solution is about 12wt%, it has a certain fluidity at high temperature and can be processed into various precise shapes using a 3D printer, or poured into a mold for arbitrary shaping. After processing and shaping, the customized GC hydrogel is further immersed in a zinc sulfate aqueous solution to obtain a GCZ hydrogel electrolyte. Figure 3 Figure a shows the customized designed GCZ hydrogel electrolyte.
[0029] Mechanical properties test of GCZ hydrogel electrolyte:
[0030] The obtained GCZ hydrogel electrolyte can be stretched and twisted to a certain extent and restored to its initial state. Figure 3 Figure b shows that a GCZ hydrogel electrolyte with a thickness of 2.0 mm and a width of 10 mm can lift a weight of 4000 g, which is about 10,000 times the weight of the GCZ hydrogel electrolyte itself. The mechanical properties of the GCZ hydrogel electrolyte sample were tested using a universal tensile machine, and its elongation at break was 266%, and the tensile stress and compressive stress were 3.0 MPa and 14 MPa, respectively. This shows that the obtained GCZ hydrogel electrolyte has excellent mechanical properties.
[0031] Conductive performance test of GCZ hydrogel electrolyte:
[0032] The impedance and instantaneous current of the GCZ gel electrolyte measured by the electrochemical workstation were used to calculate the ionic conductivity to be 5.51 S m -1 , the zinc ion migration number is 0.68.
[0033] Internal structure test of GCZ hydrogel electrolyte:
[0034] The obtained GCZ hydrogel electrolyte was freeze-dried and its internal morphology was observed using a scanning electron microscope. Figure 3 As shown in c and d, the GCZ hydrogel electrolyte has a typical porous three-dimensional network structure. Due to the Hofmeister effect, many crystalline regions are formed inside the GCZ hydrogel electrolyte, which makes the GCZ hydrogel electrolyte have excellent mechanical properties. Example 2
[0035] Preparation of GCZ hydrogel electrolyte zinc ion batteries
[0036] Preparation of positive electrode material PANI / CC:
[0037] According to the method reported in the reference (Siwen Huang, Lei Hou, Tianyu Li, Yucong Jiao*, and Peiyi Wu*. Adv. Mater. 2022, 34, 2110140.), polyaniline carbon cloth (PANI / CC) was prepared by in-situ oxidative polymerization. First, aniline monomer (0.365 mL, 0.004 M) was added to 15 mL of 1 M HCl solution and mixed evenly, and then the carbon cloth was immersed in the above aniline solution and stirred in an ice bath for 1 h. Subsequently, 5 mL of 1 M HCl solution and ammonium persulfate (0.228 g, 0.001 M) were added to the above solution, and stirring was continued for 1 h. Finally, the dark green PANI / CC positive electrode material was washed with water and ethanol, and the PANI / CC positive electrode material was dried in an oven at 60 ° C for 12 h for use.
[0038] Preparation of negative electrode material Zn / CC:
[0039] Cut a piece of carbon cloth into 1.5cm 2 The carbon cloth was taken out and washed three times with deionized water. The washed carbon cloth was connected to the electrochemical workstation (CHI760E) using a clamp. A platinum electrode was used as the electrode, a saturated calomel electrode was used as the reference electrode, and a mixed solution containing 1M ZnSO4 and 0.5M LiCl was used as the electrolyte for zinc plating. The input voltage was -2V and the duration was 1200s.
[0040] Preparation and performance testing of PANI / CC-GCZ-Zn / CC zinc ion full battery:
[0041] A button cell was assembled using PANI / CC as the positive electrode material, Zn / CC as the negative electrode material, and GCZ as the hydrogel electrolyte.
[0042] The capacity and coulombic efficiency of the button battery were tested using an electrochemical workstation. Figure 4 As can be seen from a, the capacity of the button battery is 0.1A g -1 The current density can reach 320mAh g -1 The high capacity, Coulomb efficiency is stable at 99.9%, and the capacity retention rate reaches 82% after 300 cycles. This shows that the PANI / CC-GCZ-Zn / CC zinc ion full battery prepared based on GCZ hydrogel electrolyte has excellent electrochemical performance and electrochemical stability. Example 3
[0043] Application display of soft pack battery
[0044] like Figure 4 As shown in Figure b, a simple soft-pack battery is made using a GCZ hydrogel electrolyte with a size of 20mm×20mm×4mm. The positive electrode of the soft-pack battery is a carbon cloth modified with polyaniline, the negative electrode is a galvanized carbon cloth, the nickel foam is used as the tab, and the outer layer is encapsulated with aluminum foil. Each soft-pack battery can generate a voltage of 1.2V, such as Figure 4 As shown in Figure c. Two soft-pack batteries connected in series can generate an output voltage of 2.4V, which can directly light up four small bulbs in parallel. Under the action of external force, the soft-pack battery is bent to different degrees, and its capacity and coulomb efficiency remain stable, which shows that the soft-pack battery prepared based on GCZ hydrogel electrolyte has good stability and has good application prospects in the field of flexible wearable electronic products. Example 4
[0045] Recycling of GCZ hydrogel electrolyte
[0046] Preparation of recycled gel electrolyte GCZ-r:
[0047] The used GCZ hydrogel electrolyte (30 g) was cut into small pieces, placed in a round-bottom flask and weighed. 15 mL of 2.0 mol L -1 Ammonia solution was added and stirred at 60 ° C for 3 hours to de-crosslink the GCZ hydrogel electrolyte to form a solution, and then the excess water in the solution was removed to ensure that the mass concentration of the recovered hydrogel was consistent with that of the original GCZ hydrogel electrolyte. Subsequently, the solution was poured into the corresponding mold and cooled to room temperature to gel to obtain GC-r hydrogel. The GC-r hydrogel was soaked in a 4M ZnSO4 solution for 12 hours to obtain a GCZ-r hydrogel electrolyte. Figure 5 Figure a shows the physical picture of the hydrogel electrolyte before and after recycling.
[0048] The recycled GCZ-r was used as the hydrogel electrolyte, PANI / CC was used as the positive electrode material, Zn / CC was used as the negative electrode material, nickel foam was used as the tab, and the outer layer was encapsulated with aluminum foil to prepare a soft-pack zinc ion battery. Each soft-pack battery can generate a voltage of 1.0V, such as Figure 5 Two soft-pack batteries are connected in series to generate an output voltage of 2.0V, which can directly power the digital thermometer. Figure 5 As shown in c. Figure 5 As shown in Figure d, the recycled GCZ-r hydrogel electrolyte still has excellent electrochemical performance, and the recycling rate is higher than 80%.
[0049] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.
Claims
1. A hydrogel electrolyte, characterized in that: The hydrogel electrolyte is constructed by polymer and metal salt through Hofmeister effect, ion coordination synergy and hydrogen bonding. The metal salt is wrapped in the three-dimensional network of the hydrogel. The hydrogel is cross-linked by polymer 1 with Hofmeister effect and polymer 2 containing characteristic functional groups to form a three-dimensional network structure. The cations in the metal salt are coordinated with the characteristic functional groups in polymer 2. The anions in the metal salt are used to promote the formation of crystalline regions between polymer 1 and polymer 2. The polymer 1 is gelatin, the polymer 2 is carboxymethyl chitosan, and the cations in the metal salt are Zn 2+ , the anion in the metal salt is SO4 2- The hydrogel electrolyte is used to prepare aqueous metal ion batteries or soft-pack batteries. The used hydrogel electrolyte is soaked in an alkaline solution or an acidic solution to remove crosslinks, thereby realizing the recycling and repeated use of the hydrogel.
2. A method for preparing the hydrogel electrolyte according to claim 1, characterized in that The specific steps are: dissolving polymer 2 in deionized water, adding polymer 1, and then heating to form a uniform polymer solution, completing 3D printing and mold shaping of the polymer solution by controlling the temperature before and after gelation to obtain a hydrogel, and then immersing the obtained hydrogel in a metal salt solution to obtain a hydrogel electrolyte.
3. The method for preparing a hydrogel electrolyte according to claim 2, characterized in that: The mass ratio of polymer 1 to polymer 2 is 3-5:1, and the concentration of the metal salt solution is 3-5 mol / L.